Nontesticular cancers in relatives of testicular germ cell tumor (TGCT) patients from multiple-case TGCT families - McMaster, Mary L (Cancer Med, 2015)
Testicular germ cell tumors (TGCT) exhibit striking familial aggregation that remains incompletely explained. To improve the phenotypic definition of familial TGCT (FTGCT), we studied an international cohort of multiple-case TGCT families to determine whether first-degree relatives of FTGCT cases are at increased risk of other types of cancer. We identified 1041 first-degree relatives of TGCT cases in 66 multiple-case TGCT families from Norway and 64 from the United States (combined follow-up of 31,556 person-years). We collected data on all cancers (except nonmelanoma skin cancers) reported by the family informant in these relatives, and we attempted to verify all reported cancer diagnoses through medical or cancer registry records. We calculated observed-to-expected (O/E) standardized incidence ratios, together with 95% confidence intervals (CI), for invasive cancers other than TGCT. We found no increase in risk of cancer overall (Norway O/E = 0.8; 95% CI: 0.6–1.1 and United States O/E = 0.9; 95% CI: 0.7–1.3). Site-specific analyses pooled across the two countries revealed a leukemia excess (O/E = 6.5; 95% CI: 3.0–12.3), deficit of female breast cancer (O/E = 0.0; 95% CI: 0.0–0.6) and increased risk of soft tissue sarcoma (O/E = 7.2; 95% CI: 2.0–18.4); in all instances, these results were based on small case numbers and statistically significant only in Norway. While limited by sample size and potential issues relating to completeness of cancer reporting, this study in multiple-case TGCT families does not support the hypothesis that cancers other than testis cancer contribute to the FTGCT phenotype.